Sentra Nasima Learning Strategies to Enhance Religious Nationalist Characters in Kindergarten (Universitas Negeri Semarang, 2019)
The challenge of globalization put character education as an important part of realizing quality human beings. The purpose of this study was to describe the learning strategies of sentra nasima kindergarten school in developing religious nationalist characters among students. Subjects in this study were children aged 5-6 years who attended Nasima Kindergarten. The research design uses qualitative research using the CIPP model. Data collection techniques use observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation, and conclusion drawing. The validity of the data is justified by means of technical triangulation and source triangulation. Learning strategies to enhance nationalistic characters of 5-6 year olds in sentra nasima kindergarten include: performing flag ceremonies, respecting flags, singing Indonesian Raya songs, singing compulsory songs, wearing traditional Javanese clothes (for female students wearing kebaya clothes and jarik skirts), while for male students wearing sorjan clothes, black cloth pants and blangkon accessories), wearing red and white pins, wearing batik clothes, national holidays, playing traditional musical instruments, playing national custom puppets, watching films about nationalism, playing puzzel batik patterns, playing pandhawa puppets, playing punokawan puppets, singing folk songs from various regions in Indonesia, reading reading books about nationalist characters, and dancing traditional dances from various regions in Indonesia. Learning strategy to enhance religious character in children aged 5-6 years in sentra nasima kindergarten, among others: practice wudhu, practice sholat together, dzikir together, prayer together, make giving charity to be their habit, practice saving to buy sacrificial animals, learn to recite hijaiyyah, memorizing short Hijaiyyah letters, memorizing hadiths, memorizing daily prayers, praying for sick friends, visiting orphanages, commemorating Islamic holidays, fasting at school, gathering with neighbors around Nasima Kindergarten, and munaqosah (public test of the increase in volumes of the Qur’an recitation). Efforts to enhance nationalist and religious character at the sentra nasima are carried out through a process of intervention and habituation. Character education is carried out in three domains. First, the development of nationalist and religious character values that are integrated into teaching and learning activities in the middle class. Second domain, integrating character education with extracurricular activities and school culture. The third domain involves student guardians to help build habituations that are in line with those developed in schools.